Sheep tolerance to sodium hydroxide and/or residual contents in the broiler litter - Barros, Nelson Nogueira; Sanchez, Luiz Maria Bonnecarrere; Lopes, Jourez Mosbini (Pesquisa Agropecuaria Brasileira, 2014)
Sheep tolerance to sodium hydroxide (NaOH) treated diets was studied. Eighteen Corriedale sheep were used in a completely randomized block design, with a 2 x 3 factorial arrangement. The design included two types of broiler litter (one composed of rice hulls and the other one of rice straw) and three levels of NaOH (zero, 6% and 12%). Water and Na intakes, urine excretion and Na: K urinary ratio, increased (P < 0.05) as the NaOH treatment level increased. The urinary density decreased (P > 0.05) when yield increased. The urine pH showed only a tendency of increasing when the alkali treatment in the animal diet increased. No effect of the NaOH treatments on the ruminal pH was detected. Sodium balance was negative and inversely related to the Na intake. However, there were not enough data for a clear explanation of this fact.